Neuromuscular fatigue during prolonged exercise in hypoxia - Jubeau, M.; Rupp, T.; Temesi, J.; Perrey, S.; Wuyam, B.; Millet, G. Y.; Verges, S. (Medicine & Science in Sports & Exercise, 2017)
Purpose: Prolonged cycling exercise performance in normoxia is limited because of both peripheral and central neuromuscular impairments. It has been reported that cerebral perturbations are greater during short-duration exercise in hypoxia compared with normoxia. The purpose of this study was to test the hypothesis that central deficits are accentuated in hypoxia compared with normoxia during prolonged (three bouts of 80 min separated by 25 min) whole-body exercise at the same relative intensity.